A non-profit organization: essence, types and basic business processes (Economics and region, 2020)
The essence, types, signs and functions of non-profit organizations are investigated. The processes needed to be provided for effective functioning of a non-profit organization are identified. World experience of non-profit organizations’ possibility to carry out business activities in the practice of different countries is analyzed. The market economy involves the active development of non-profit organizations that arise and operate in various sectors of the economy (education, culture, art, services, etc.). The role of the so-called "third sector" is important for civil society development, so we see the intensification of non-profit organizations around the world. These organizations play important role in achieving sustainable development goals, providing charitable assistance, protecting human rights and freedoms, organizing leisure time, creating opportunities for human development, helping to solve many social issues and challenges, providing cultural, educational and other services. The definition of "non-profit organization" is used mainly in American law, while in international practice the definition of "non-governmental organization" is often used. This emphasizes that the organization focuses on solving social problems, has a humanitarian purpose and is independent from the government. The definition of "non-profit organization" provides a special approach to the functioning of the organization and its taxation. The purpose of the organization is not to make a profit, but to ensure organizational development. Non-profit enterprises, institutions and organizations are enterprises, institutions and organizations main purpose of which is not to make a profit, but to conduct charitable activities and patronage, as well as other activities provided by law. These activities are aimed at providing charitable assistance, educational, cultural, scientific, educational and other similar services for public needs.
Keywords: administration; business processes; management; non-profit organization; function